2007
DOI: 10.1007/s11244-007-0322-8
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of PDDA stabilized Au–Pd bimetallic nanostructures and their activity in hydrogenation of acetylene

Abstract: Pd hydrosol was synthesized by reducing PdCl 2 solution with dissolved H 2 in the presence of PDDA [poly(diallyldimethylammonium chloride)] as ionic stabilizer. O 2 treatment resulted in the reappearance of ligand to metal charge transfer bands of PdCl 4 2). Repeated oxidation and hydrogen treatments caused aggregation/agglomeration of the Pd particles yielding big spherical aggregates of 30-50 nm but still keeping the size of the 5-6 nm primary particles. Aggregation was attributed to the reduction of PdCl 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…One means is to dope the Au catalyst with a second metal. In particular, supported Au-Pd catalysts have been widely studied in selective hydrogenation of acetylene [4][5][6][7][8]. Besides, it is easy for Au and Pd to form alloy, thus the interaction between Au and Pd will not only be beneficial to the activity but also keep a high selectivity of ethylene at the same time during hydrogenation of acetylene to ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…One means is to dope the Au catalyst with a second metal. In particular, supported Au-Pd catalysts have been widely studied in selective hydrogenation of acetylene [4][5][6][7][8]. Besides, it is easy for Au and Pd to form alloy, thus the interaction between Au and Pd will not only be beneficial to the activity but also keep a high selectivity of ethylene at the same time during hydrogenation of acetylene to ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that gold nanoparticles supported on TiO 2 or Fe 2 O 3 catalyze the selective reduction of a nitro group in substituted nitroaromatics under mild reaction conditions [8] opened a way to substitute these environmentally non sustainable processes by others based on the use of easily recyclable solid catalysts and H 2 as reactant. However, the activity of the original Au/TiO 2 and Au/Fe 2 O 3 materials toward hydrogenation is too low for practical applications [9,10] and attempts to design more efficient catalysts have been done which include the analysis of gold particle size dependence [11], the use of different supports for the gold nanoparticles [12][13][14][15][16][17], alloying gold with traditional hydrogenation metals such as Pd [18][19][20] or Pt [21], or directly preparing nanoparticles of other highly active transition metals such as Pt, Ru or Ni [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…According to Sarkany et al, Au/Pd molar ratio of 20/80 in core/shell-structured NPs exhibited the highest catalytic activity for the hydrogenation of acetylene. [3] Ishihara et al [11] also reported that bimetallic NPs of Au/Pd ratio of 19/81 immobilised on rutile TiO 2 showed superior performance for hydrogen peroxide synthesis by hydrogen oxidation with O 2 . It is interesting that the optimum ratios are comparable irrespective of the reaction systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among bimetallic NPs, Au-Pd NPs have attracted much attention mainly in the field of catalysts. [1][2][3] The synergistic effects of the addition of Au to Pd in enhancing the overall catalytic activity, selectivity and stability of the catalyst have been of great interest. Goodman et al [4] investigated the effect of the addition of Au using acetoxylation of ethylene and concluded that the critical reaction site for vinyl acetate synthesis consisted of two non-contiguous Pd monomers suitably spaced by Au.…”
Section: Introductionmentioning
confidence: 99%